Impact of perceived e-service quality towards customer engagement on e-commerce platform among generation Z in Malaysia - Oon, Bennet Wei Sharn; Chan, Chen Meng (2023)
Convenience is key in today's environment because the Internet is intertwined with everything. This has propelled the success of e-commerce to new heights. This double-edged sword has brought upon distractions to e-commerce customers from other forms of entertainments. What is left is a short among the generation Z customers. Generation Z Malaysians take up 29% of the Malaysian population, making it the largest age group. While still being technologically dependent and attention deficient. E-service quality can improve customer’s overall associations towards a platform and influencing their perception of the platform to achieve customer engagement. E-S-QUAL model was applied in this research to discover the impact of e-service quality towards customer engagement on e-commerce platforms among Generation Z in Malaysia. It is the most commonly used and externally validated scale in the context of e-service quality. The four independent variables were derived from the model which are efficiency, fulfilment, privacy and system availability. The four hypotheses were constructed to identify if these variables have an effect on customer engagement on e-commerce platforms. The sample size for this study is 400 Generation Z e-commerce users (18–25-year-old) as the target respondents. The questionnaire was implemented with reliability test and validated with construct validity and content validity. The results were analysed with the use of Statistical Package for the Social Sciences (SPSS). Inferential analysis method was employed using Pearson Correlation Coefficient and Multiple Linear Regression to identify the relationship between the independent variables and dependent variable in this study. The main limitation of the study is the use of convenience sampling which did not accurately represent the population demographic to increase the accuracy of the study's findings.